A Changing China : Implications for Developing Countries - Schellekens, Philip (World Bank, Washington, DC, 2013)
Three decades of rapid growth and structural change have transformed China into an upper-middle-income country and global economic powerhouse. China's transformations over this period wielded increasing influence over the development path of other countries, either directly through bilateral trade and financial flows or indirectly through growth spillovers and terms of trade effects. Looking ahead, as China embarks on a new phase in its development journey, a phase characterized by slower but higher-quality growth, the economic landscape facing the developing world is expected to be redefined yet again. As China changes, so will its interactions with the outside world. China is expected to remain both a market and a competitor, but its changes are likely to lead to new opportunities for many and new challenges for some. Key questions in this respect are: (i) how will the level and composition of China's import demand evolve as its economy slows and rebalances; (ii) to what extent will the presumed out-migration of labor-intensive manufacturing materialize and create new opportunities elsewhere; and (iii) how quickly will China move up the value chain and redefine its competitive advantage in the global marketplace? How these uncertain long-term developments affect individual countries will depend on differences in total supply chain costs, resource availability, and innovation capability. As in the past, China's transformations are expected to put formidable pressure on countries to adapt and reform, requiring both political will and entrepreneurial capacity, in a collective race where success will be measured against a rapidly moving frontier.